(untitled) (The Peerian Journal, 2022)
Based on the thermal processing of biowaste, it is possible to obtain various energy fuels and use these fuels for energy purposes. With the help of biomass, it is possible to provide reliable energy to greenhouses, domestic enterprises and rural households, and at the same time, to provide reliable energy to regions that do not have access to energy. Biomass is a renewable resource that can solve problems such as saving natural resources and rising oil prices. Flexibility and efficiency in production are key principles for biomass conversion technologies in future energy systems. In this article, it is stated on the basis of analysis that thermal processing of biomass is highly flexible and optimal use is effective.